Can a Beard Speak Truth? Exploring Its Role in Muslim Intellectual and Cultural Identity - Maspul, Kurniawan Arif; Mubarak, Islahuddin Ramadhan (Pubmedia Social Sciences and Humanities, 2025)
The Muslim beard, far more than facial hair, emerges as a dynamic symbol of faith, intellect, and resistance in a globalized world. Rooted in prophetic injunctions to “trim the moustache and grow the beard” (Sahih Muslim), this practice transcends grooming to embody Sunnah adherence, fitrah (natural disposition), and communal identity. Drawing on qualitative analysis of classical jurisprudence, sociological theories, and ethnographic interviews across the Middle East and Southeast Asia, this study reveals the beard as “lived theology” (de Rooij, 2020)—a marker of piety, scholarly gravitas, and political dissent. In Egypt, post-2011 beard-wearing symbolized reclaiming public space (Fahim, 2012), while Tajikistan’s 2015 crackdown, shaving 13,000 men (U.S. Commission on Religious Freedom, 2024), underscores its weaponization. Regionally, the beard adapts: from Gulf clerical authority to Southeast Asia’s blend of trimmed beards and songkok caps (Olivier, 2018). The study challenges homogenizing narratives, advocating for policies that respect diversity (e.g., Malaysia’s civil-service guidelines) and educational initiatives linking the beard to Islamic ethics and sustainability. This work sheds light on the function of the beard in negotiating modernity, facilitating interfaith discourse, and regaining Muslim identity in the face of secular and Islamophobic forces. It calls for stakeholders—educators, imams, policymakers—to transform this ancient tradition into a resilient, ethical emblem for the 21st century.